The origin of Electric Charge carried by Thunderstorm Rain in the Tropics - SIVARAMAKRISHNAN, M. V. (MAUSAM, 1961)
A detailed study of the electricity carried by thunderstorm rain has been made at the Poona Meteorological Office, during four years 1955-1958. The study consists in considering the three stages in the life history of raindrops, namely, (I) the growth of the drop within the cloud and the possible acquisition of electric charges, (2) the period of free fall below the cloud with the possible modification of charge of rain by capture point discharge ions as per theories advanced by Whipple and Chalmers and (3) the arrival at the ground With the possible effects of splashing at the ground. It is concluded that the electricity of thunderstorm rain is not always due to any single process of generation of charge, and that several factors such as the impact of ice crystals, the breaking of drops, as per theories advanced by Simpson and Scrase, the Wilson mechanism the effect of lightning discharge, may operate together to determine what shall be the sign of the charge thunderstorm rain when it reaches the ground. It is also proved that charging of the rain due to splashing at the surface does not occur, as the rain receiver is suitably shielded to avoid splashing.